(untitled) (Ozone Therapy Global Journal, 2011)
Retinitis Pigmentosa (RP) is characterized by bad night vision, decrease of visual field and/or acuity, with electroretinogram (ERG) diminished in amplitude and finally, non reproducible. Taking into account some of the ozone biological effects, as: improvement in the oxygen metabolism, increase in the cell energy, the immunomodulator capacity and enhancement of the antioxidant defense system the aim of this paper is to assess ozone therapy’s efficacy i n these patients, treated twice a yea r during 20 years . A cont r olled and retrospect i ve clin i cal s tudy was performed in 56 patients with Typical Retinitis Pigme ntosa (non-associa ted) , with sample homogeneity, in age, sex and stage of the disease, and with signed informed consent. Forty patients received ozone daily, by rectal way, during 20 sessions (at a concentration of 40 mg/L and a volume of 200 mL) as only treatment, w i th repe tition of this cy cle every 6 m onths, a nd 16 rec e i ved other medical treatmen ts (control group). Resul ts showed that , after 10 years, patients in stages I and II h ad a better r esp onse to ozone therap y, a nd th i s response was more la sting, with an improvement attained as of 4 months, which is the shortest time period for patients in stages II and IV. After 20 years of treatment, 50.1 % of patients improved their visual field, 31.1 % remained the same and 18 % followed the course of the disease. In respect to visual acuity, we observed that 37.5% of patients improved, 34.9 % remained stable and 27.6 % continued the course of the disease. It is recommended to apply ozone therapy at six-month intervals in order to delay the course of the disease and maintain the visual capabilities. No side effects were observed. Ozone therapy is a good therapeutic choice in the treatment of patients with RP increasing their quality of life.